Environmental retrieval during COVID-19 lockdown in the megacity Karachi, Pakistan - Ali, Nida; Kausar, Anila; Vambol, Sergij; Kozub, Pavlo; Kozub, Svetlana (Ecological Questions, 2024)
The global devastating effect of COVID-19 has also wrapped up the mega city of Pakistan-Karachi. The study was conducted to reveal the effects of limited anthropogenic activities, in terms of national lockdown, on the environmental pollution in Karachi. No study has been conducted to monitor the effect of the COVID-19 lockdown on levels of PM2.5 and noise in Karachi so far. The levels of PM2.5 and noise were monitored before and during the imposition of the COVID-19 lockdown with the help of a particulate monitor and environmental meter, respectively. The monitoring was conducted for 12 hours at 25 locations. The spatial distribution of mean PM2.5 and noise levels were represented by thematic maps. Statistical evaluation revealed a significant decrease in PM2.5 and noise pollution by 53.55% and 24.98%, respectively. The percentage of locations where the mean PM2.5 level was surpassing the Sindh environmental quality standards before the lockdown had dropped from 56% to 8% during the lockdown. Similarly, the percentage of locations where the mean value of noise exceeded the standard values before lockdown had descended from 96% to 24 % for residential areas; 72% to 12% for commercial areas; and 44% to 0% for industrial areas, during lockdown.